Perancangan Media Pembelajaran Mengenal Huruf Arab (Hijaiyah) untuk Anak Usia 4-6 Tahun dengan Menggunakan Software Pengolah Animasi 2 Dimensi - Titania Dwi Andini; Achmad Bahar Wafa (Jurnal Desain Komunikasi Visual Asia, 2017)
This learning media is very useful because it helps Children at 4-6 years of age can more easily receive thematerial that is taught in addition to also make the children interested to learn the material delivered. In thislearning media will be delivered is about the Arabic Letters (Hijaiyah) . More aimed at children at 4-6 yearsold, because in children aged 4-6 years is very easy and quick to memorize from what they see and learn.The sophistication of technology now allows anyone to learn to make learning media such as 2-dimensionalanimation processing software, Macromedia Flash and vector image processing software, Corel Draw. Thislearning media has an interesting concept, from the material it conveys easily understood, coupled withunique character and background image will make the children unsaturated to learn it and understand thecontents of the material presented.